Emerging Feminist Peace from Below and Disaster Recovery: Complex Cascades of Violence and Uncertainty as a Result of Earthquake Recovery - Dwi Rahayu Nurmiati; Binahayati Rusyidi; Budi Muhammad Taftazani (The Journal of Indonesia Sustainable Development Planning, 2025)
Disasters are rarely neutral; their impacts, responses, and recoveries are filtered through social, political, and economic structures that determine who is protected, who is excluded, and who gets to rebuild (Few et al., 2021). In many contexts, particularly in the Global South, post-disaster recovery processes become sites of contestation where inequality is not only revealed but reinforced (Joseph et al., 2021). Emerging Feminist Peace from Below and Disaster Recovery: A Quilted Ethnography by Marjaana Jauhola and Shyam Gulhavi provides an incisive and unconventional lens into these processes. The book is a landmark contribution to feminist peace studies and disaster ethnography, bringing forward a textured narrative of post-earthquake recovery in Gujarat, India, with direct relevance to broader debates on sustainable development, spatial justice, and inclusive planning.